PENGARUH PENGALAMAN KERJA DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BPR BATURAJA - Erfin Mardalena; Noviansyah Noviansyah; Darman Syafe'i; Nur Anita Yulia Sari (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
The influence of work experience and promotion on job satisfaction of employeesat PT. BPR Baturaja. The data collection technique used in this study wasthrough the distribution of questionnaires. The population was 56 people. Thedata analysis technique used was Multiple Linear Regression. Based on partialanalysis results, there was an influence of work experience on the job satisfactionof employees at PT. BPR Baturaja with a t count value of 4,580. The promotionvariable had an influence on the job satisfaction of employees at PT. BPRBaturaja with a t count value of 5,212. Simultaneously was obtained the influenceof work experience and promotion on the job satisfaction of employees at PT.BPR Baturaja with a F count value of 43,394. The coefficient of determination(R2) obtained was 0.621. This meant that the contribution of the influence of workexperience and promotion on job satisfaction was 62.1%, while the rest 37.9%was influenced by other variables outside this study, such as intelligence, physicalcondition, personality and way of thinking (Mangkunegara, 2015:120).